Kedudukan Dan Perlindungan Hukum Penyandang Disabilitas Dalam Pewarisan - Fitria Dewi Navisa (Arena Hukum, 2022)
This research aims to whether in the legislation a person with a disability who is under guardianship is also a legal subject who has the right to obtain inheritance rights as an heir. This juridical normative research is intended to understand legal protection of civil rights for heirs (with disabilities) who are under guardianship. The results shows that if a person is not able to take care of himself, in this case is a person with a disability, then it is necessary to provide amnesty, because in the process of inheriting a person with a disability is considered incapable and his position is equal to an immature person, then the facilitator must be assisted to receive an inheritance, so that he does not lose the inheritance rights. Applications to become “curatele” can be submitted at the District Court / Religious Court for Muslims in their respective jurisdictions. In terms of obtaining the right to inherit, there are legal protection for the heirs of disabilities persons in the Private Law Act and Act Number 8 of 2016 concerning Persons with Disabilities.